The effect of cultural and social responsibility on entrepreneurial resilience among immigrant entrepreneurs in Johannesburg - Ntlakana, Anelisa (My University, 2023)
Amidst the increasing amount of immigrant entrepreneurship studies, as well as the constantly growing number of immigrant entrepreneurs in South Africa and their potential impact on the South African socioeconomic , immigrant entrepreneurs' beliefs and practices of cultural and social responsibility, as well as how this affects their resilience, are still understudied. This research’s focus is on (i) the relationship between culture, social responsibility, and immigrant entrepreneurial resilience, (ii) how immigrant entrepreneurs interpret culture and social responsibility, and (iii) the impact of demographic factors on entrepreneurial resilience of immigrant entrepreneurs in the informal sector context in South Africa. Furthermore, in terms of resilience, this study investigated the impact of immigrant entrepreneurs' awareness of government assistance programs on their resilience. The study was quantitative, with 180 immigrant business owners working in the informal sector in Johannesburg being polled using accessible sample procedures. The findings show that both dimensions of social responsibility (philanthropy and ethic) had a significant relationship with entrepreneurial resilience, whereas, only one dimension of culture (ubuntu) had a significant relationship with entrepreneurial resilience, furthermore, the study also found that awareness of government support had a significant positive impact on entrepreneurial resilience of immigrant entrepreneurs in Johannesburg's informal sector. Theoretical contribution: This study contributes to the increasing literature on social responsibility and immigrant entrepreneurship by exploring social responsibility from the perspective of an informal immigrant entrepreneur. This study sheds light on how informal immigrant businesses view community social responsibility and how it has improved their resilience. Practical contribution: This research outlines activities in which informal immigrant business owners can engage and use to enhance their resilience in the informal sector, where they encounter challenges such as a lack of financial support. In addition, the research recommends that government agencies incorporate immigrant entrepreneurs into their strategic and operational frameworks. Entrepreneurs who are new to the Republic of South Africa are encouraged to look for government aid programs on their own.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Immigrant entrepreneur; Philanthropy; Informal sector; SDG-8: Decent work and economic growth